1990
DOI: 10.1073/pnas.87.15.5993
|View full text |Cite
|
Sign up to set email alerts
|

Platelet-derived growth factor stimulates formation of active p21ras.GTP complex in Swiss mouse 3T3 cells.

Abstract: The ras gene product (p21) is a GTP-binding protein and is thought to play an important role in signal transduction of growth and differentiation in many types of mammalian cells. The p2FGTP complex is an active conformation, as described previously for polypeptide chain elongation factors (EF-Tu and EF-G) and heterotrimeric GTPbinding proteins (G proteins). In the study reported here, we measured the amounts ofp21-bound guanine nucleotides under various conditions in the G54 cell line, a derivative of Swiss 3… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

8
139
0

Year Published

1992
1992
2007
2007

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 256 publications
(147 citation statements)
references
References 39 publications
8
139
0
Order By: Relevance
“…We found that the activation state of Rap 1 was *13% in parental HL-60 cells in a serum-starved nonstimulated state which is very similar to the 14% Rap 1B activation reported in serum-starved nonstimulated PC-12 cells transfected with poly-histidinetagged Rap 1B and metabolically labeled with 32 PO 4 (Vossler et al, 1997). This degree of Rap 1 activation is higher than we (Scheele et al, 1995) and others (Satoh et al, 1990) have found for basal activation of wild type non-mutated Ras and may be attributed to the threonine in position 61 of Rap 1 which decreases the intrinsic GTPase activity of Rap 1 10-fold compared to Ras (Kitayama et al, 1989;Hart and Marshall, 1990). We found the activation of endogenous Rap 1 in HL-60 cells to be similar to the activation of transfected Rap 1A in BHK cells; to avoid saturation of endogenous RapGEFs and RapGAPs, the transfected Rap 1A was expressed at relatively low levels in the BHK cells (as determined by immunoblotting (data not shown) and by comparing total nucleotide-bound Rap1 in HL-60 cells to that of transfected Rap 1A in BHK cells (Tables 1 and 2)).…”
Section: Discussionsupporting
confidence: 85%
“…We found that the activation state of Rap 1 was *13% in parental HL-60 cells in a serum-starved nonstimulated state which is very similar to the 14% Rap 1B activation reported in serum-starved nonstimulated PC-12 cells transfected with poly-histidinetagged Rap 1B and metabolically labeled with 32 PO 4 (Vossler et al, 1997). This degree of Rap 1 activation is higher than we (Scheele et al, 1995) and others (Satoh et al, 1990) have found for basal activation of wild type non-mutated Ras and may be attributed to the threonine in position 61 of Rap 1 which decreases the intrinsic GTPase activity of Rap 1 10-fold compared to Ras (Kitayama et al, 1989;Hart and Marshall, 1990). We found the activation of endogenous Rap 1 in HL-60 cells to be similar to the activation of transfected Rap 1A in BHK cells; to avoid saturation of endogenous RapGEFs and RapGAPs, the transfected Rap 1A was expressed at relatively low levels in the BHK cells (as determined by immunoblotting (data not shown) and by comparing total nucleotide-bound Rap1 in HL-60 cells to that of transfected Rap 1A in BHK cells (Tables 1 and 2)).…”
Section: Discussionsupporting
confidence: 85%
“…Assuming that c-Crk is linking insulin-and PDGF-induced signaling pathways to Ras activation, our data demonstrate that insulin and PDGF dependent pathways di er in the requirement for MAP kinase activation. Work from several laboratories has indicated that the level of GTP-bound Ras increases following PDGF stimulation of cells (Gibbs et al, 1990;Satoh et al, 1990;Nanberg and Westermark, 1993;Maruta and Burgess, 1994). In cells expressing wild-type PDGF receptor, PDGF stimulation resulted in an approximate twofold increase in the GTP content of Ras, with only 5% of GTP versus 95% of GDP following immunoprecipitation with anti-Ras antibodies .…”
Section: Discussionmentioning
confidence: 99%
“…Details of procedures were described elsewhere (Satoh et al, 1990a). Brie¯y, SE cells were labeled for 6 h with 0.1 mCi/ml 32 P-orthophosphate in phosphate-free DMEM.…”
Section: Ras Assaymentioning
confidence: 99%